Sintomatologia depressiva em pacientes com tuberculose na região metropolitana do Espírito Santo - Silva, Teresa Cristina Ferreira da (2020)
Objective: To describe the clinical and socio-economic profile, and the depressive symptoms of people undergoing tuberculosis treatment in the metropolitan region of the state of Espírito Santo, Brazil. Methodology: This is a descriptive, cross-sectional study carried out between August 2019 and March 2020, within the scope of primary care in municipalities of the metropolitan region of Espírito Santo. Socio-economic, behavioural, and clinical data were collected through an interview, and the depressive symptoms were tracked by the Patient Health Questionnaire-9 (PHQ-9). Results: The sample consisted of 92 patients, mostly male, non-white, 41.5 years old (average), half of which were single, without complete elementary school, unemployed, with a family income of up to 3 minimum wages, belonging to the socio- economic classes C, D and E, and not covered by a cash transfer program. 48% of the sample with depressive symptoms were screened, with 81% in a severity level ranging from mild to severe, with predominance of the symptom of fatigue (84%) and the presence of a depressed mood and anhedonia in 58%. Conclusion: Depressive symptoms in the studied population showed a relevant and potential frequency to harm the personal, social and health status of people undergoing tuberculosis treatment. Thus, in the perspective of the National Plan for the End of Tuberculosis, tracking depression or its manifestations can expand the care and prevention actions focused on the patient with tuberculosis and reduce the combined effects of tuberculosis and depression